The Influence Of Work Facilities And Work Placement On Work Performance Of Pt. Masa Mitra Pratama Medan - Caroline Iewanto; Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (Institute of Computer Science (IOCS), 2022)
PT. Masa Mitra Pratama is a company engaged in the service and sale of banking electronic needs such as: money counting machines, teller machines, and others who started their business in 2007 and continues to grow by opening various branches, one of which is located in Medan. Employees cannot perform well at work such as: in terms of quality, employees often make mistakes in completing their work. The company does not provide adequate facilities for its employees. Employee work placements in the company are still not in accordance with the criteria or abilities possessed by employees, making employees slow to work. This research uses quantitative descriptive research. The research population that will be used in the study is all employees who work at the company as many as 41 employees. Determination of the research sample using saturated sampling. Simultaneously there is a significant influence between the variables of work facilities and work placement on the work performance of PT. Masa Mitra Pratama . While partially found the variable work facilities have a significant effect on the work performance of PT. Masa Mitra Pratama . Partially it was found that the work placement variable had a significant effect on the work performance of PT. Masa Mitra Pratama . The results of this study indicate that the variable work facilities have more influence than work placement on the work performance of PT. Masa Mitra Pratama